Evaluation of the Transfer of Responsibility for Child Protective Services to Law Enforcement in Manatee, Pasco, and Pinellas Counties, Florida, 1995-2001 - Kinnevy, Susan C. ([Verlag nicht ermittelbar], 2004)
In 1998 Florida law required that the responsibility for child maltreatment investigations be transferred from a statewide child welfare agency to the sheriff's offices in Manatee, Pasco, and Pinellas Counties. The aim of this study was to evaluate the outcomes produced by this change. This study used a nonequivalent control group design. Performance in Manatee, Pasco, and Pinellas Counties was compared to performance in selected counties before and after the change in service took place. Data were obtained from the Florida Abuse Hotline Information System (FAHIS), an online data system that contained records of all reported incidents of abuse and neglect in the state of Florida.